Faktor-Faktor Yang Mempengaruhi Deposito Mudharabah Pada Bsi Kcp Stabat Proklamasi - Fitriyani; Tambunan, Khairina (Medan Resource Center, 2022)
This study aims to examine the effect of profit-sharing ratio, tax, and FDR on mudharabah deposit customers at BSI Kcp Stabat Proklamasi. This research was conducted at BSI Kcp Stabat Proclamation. The research method used is a quantitative method with primary data. The primary data analyzed are data on the number of mudharabah deposit customers, profit sharing ratios, taxes, and monthly FDR for 1 (one) year which are taken at BSI Kcp Stabat Proclamation. Based on the results of the simultaneous test (F test), the independent variables (profit sharing ratio, tax, and FDR) have no simultaneous or simultaneous effect on the amount of mudharabah deposits. So that the increase or decrease in the number of mudharabah deposits has no effect on the profit sharing ratio and taxes, the amount of FDR will most likely be affected.